2016
DOI: 10.2139/ssrn.2796566
|View full text |Cite
|
Sign up to set email alerts
|

Online and Offline Information for Omnichannel Retailing

Abstract: This paper studies how retailers can effectively deliver online and offline information to omnichannel consumers who strategically choose whether to gather information online or offline and whether to buy products online or offline. Information resolves two types of uncertainty: product value uncertainty (i.e., consumers realize valuations when they inspect the product in store, but may end up returning the product when they purchase online) and availability uncertainty (i.e., store visits are futile when cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…In terms of disciplinary orientation, these studies contribute to the omnichannel literature with respect to supply chain, retailing and marketing domain. Those that focus on supply chain tend to emphasize different functions and drivers including distribution and fulfilment (Melacini et al., 2018), delivery (Buldeo Rai et al, 2019a), facilities (Bell et al., 2017; Kembro et al., 2018), information technology (Gao & Su, 2017b), network design (Yadav et al., 2019), return management (Akturk et al., 2018; Bernon et al., 2016), logistics (Wollenburg et al., 2018b). In contrast, marketing‐focused studies placed a particular emphasis on channel management (Hosseini et al., 2018; Jocevski et al., 2019), product recommendation (Balakrishnan et al., 2018), pricing (Harsha et al., 2019), promotion (Blom et al, 2017) and sales management (Cummins et al., 2016).…”
Section: Research Findings and Analysismentioning
confidence: 99%
“…In terms of disciplinary orientation, these studies contribute to the omnichannel literature with respect to supply chain, retailing and marketing domain. Those that focus on supply chain tend to emphasize different functions and drivers including distribution and fulfilment (Melacini et al., 2018), delivery (Buldeo Rai et al, 2019a), facilities (Bell et al., 2017; Kembro et al., 2018), information technology (Gao & Su, 2017b), network design (Yadav et al., 2019), return management (Akturk et al., 2018; Bernon et al., 2016), logistics (Wollenburg et al., 2018b). In contrast, marketing‐focused studies placed a particular emphasis on channel management (Hosseini et al., 2018; Jocevski et al., 2019), product recommendation (Balakrishnan et al., 2018), pricing (Harsha et al., 2019), promotion (Blom et al, 2017) and sales management (Cummins et al., 2016).…”
Section: Research Findings and Analysismentioning
confidence: 99%
“…Herhausen, Binder, Schoegel, and Herrmann () found that online–offline channel integration can yield a competitive advantage for the retailer by influencing consumers’ perceived service quality and perceived risk of the online store. Gao and Su () further suggested that the omni‐channel consumers’ valuation uncertainty can be resolved by information delivery through both physical and virtual showrooms. In this article, by capturing consumers’ omni‐channel showrooming behavior that utilizes the offline information service, we go beyond the studies of Ofek et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, by capturing consumers’ omni‐channel showrooming behavior that utilizes the offline information service, we go beyond the studies of Ofek et al. () and Gao and Su () by examining the retailer's information service provision in the physical stores. In addition, we study the M‐R information service compensation and its corresponding impacts on the players, which generates implications of information service provision for the omni‐channel supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…The professional setting is important because it implies that the professional must herself deliver service via the new channel instead of offloading it to another server. This idea of a single server dealing with multiple channels as they become introduced is new and contrasts with much of the current literature, which has focused more on how new service channels affect “non‐professional” servers such as those in retail (Bell, Gallino, & Moreno, ; Gallino & Moreno, ; Gao & Su, ). The professional setting is also unique because such servers typically have control over much of their workflow (Harvey, ), forcing them to individually reoptimize their workflow when a new service delivery channel is introduced.…”
Section: Introductionmentioning
confidence: 99%